Fetomaternal Outcome of Pregnant Women with Malaria : Fetomaternal Outcomes of Pregnant Women - Mehwish, .; Memon, Mehreen; Solangi, Bakhtawar; Erum, .; Raishem, .; Farzana, .; Tosheeba, .; Maheshwary, Neeta (Pakistan Journal of Health Sciences, 2025)
Malaria during pregnancy is a major public health concern, with devastating implications for both the mother and the unborn child. Objectives: To evaluate the maternal and fetal outcomes in pregnant women infected with Plasmodium falciparum and Plasmodium ovale/vivax. Methods: This descriptive cross-sectional study was carried out in Obstetrics and Gynecology Ward II using non-probability convenience sampling. It included 110 pregnant women diagnosed with malaria, excluding those with underlying health conditions. Data were gathered through interviews, medical records, and laboratory tests. Various maternal and neonatal factors, including hemoglobin levels and birth weight, were recorded. The chi-square test was performed to evaluate the relationship between malaria and fetal outcomes, with p-values<0.05 considered statistically significant. Results: Among 110 pregnant women, 58 (52.7%) were aged 21–30 years. The majority, 69 (62.7%), had 2–5 pregnancies, while 25 (22.7%) were primigravida. Preterm birth and full-term deliveries were equally distributed, 55 (50.0%), while anemia was prevalent in 82 (74.5%) of cases. Low birth weight was observed in 35 (31.8%) of neonates. Among 71 women with P. falciparum infection, 63 (88.7%) developed anemia, which was significantly higher than in the P. ovale/vivax group, where only 19 out of 39 (48.7%) were anemic (p<0.001). Preterm birth, 45 (63.4%) and low birth weight, 34 (47.9%), were significantly greater in falciparum cases (p<0.001). Conclusions: It was concluded that Plasmodium falciparum infection poses a higher frequency of adverse fetomaternal outcomes compared to Plasmodium ovale/vivax, characterized by noticeably greater incidences of hypoglycemia, low weight at birth weight, premature birth, and anemia.